Apuntes para una historia de las becas de la Fundación Guggenheim para América Latina - Quesada, Fernando; Gallardo, Osvaldo (El Colegio de México, 2024)
The John Simon Guggenheim Memorial Foundation fellowships played an important role in catalyzing the mobility of ideas, knowledge and imaginaries between Latin America and the United States from their creation in 1930 until their closure in 2011. In these notes we approach to this fellowship program from four dimensions: historical, geographical/spatial, operational and individual, with the aim of conducting an exploratory study of a phenomenon that has not received attention from social studies.